Application of Solar-Based Light Lumen to Papuyu Fish Farmers in Penggalaman Village, West Martapura: Indonesia - Dwi Kartini; Nugrahadi, Dodon Turianto; Ramadhani, Rahmat (UII, 2024)
Penggalaman Village, West Martapura, Banjar Regency, South Kalimantan is one of the papuyu fisheries development areas. The location of the village is very strategic, located along the irrigation flow of Penggalaman Village and has very sufficient potential in the fisheries business for fish farmers. Villagers have carried out papuyu fish seed cultivation activities that have ponds for artificial fertilization of papuyu fish, papuyu fish egg hatching ponds and enlargement ponds but have not implemented lighting in the process of fish farming activities. This is because it requires a lot of electrical energy and costs a lot for these activities. The purpose of this service activity is to introduce and apply solar-based electrical energy sources for fish farmers in improving fisheries businesses as an alternative to electrical energy. This tool is equipped with yellow and white lumens, controller, battery, aerator and solar panel and automatic control system. The application of solar-based lumens will provide a technological solution to the lighting of papuyu fingerlings and enlargement ponds for papuyu fish farmers in Penggalaman Village. Yellow and white lumens are able to provide lighting and reduce predator attacks at night. The results of the application of this technology are the fulfillment of electrical energy by applying solar-based lumens to papuyu fish nurseries and increasing the lighting of fish nurseries and papuyu fish enlargement by approximately 80%, and reducing night predator attacks by 70%.